Effect of peracetic acid as a depressant on the flotation separation of chalcopyrite from arsenopyrite. (15th March 2022) - Liu, Yang; Wei, Zhicong; Hu, Xianzhi; Zi, Futing; Zhang, Yan; Zeng, Ming; Chen, Yunlong; Chen, Shuliang; Bai, Rui; Xie, Zihua
Highlights: Separation of arsenopyrite from chalcopyrite hindered by similar floatabilities. Depression of arsenopyrite flotation required for better separation. Effect of peracetic acid as a depressant of arsenopyrite was investigated in this study. Found to greatly aid in flotation separation under neutral pH conditions. Abstract: Arsenopyrite is an arsenic-bearing mineral that frequently occurs with chalcopyrite in polymetallic sulphide deposits. Their separation via existing methods and reagents involved in the flotation process, however, remains sub-par due to difficulties in the effective depression of arsenopyrite. In this study, the eco-friendly organic oxidant of peracetic acid (PAA, CH3 C(O)OOH) was used for the first time ever to effectively depress arsenopyrite under conditions of neutral pH. Flotation experiments, adsorption tests, zeta potential analysis, X-ray photoelectron spectroscopy (XPS), and time-of-flight secondary ion mass spectroscopy (ToF-SIMS) were performed to investigate the depression mechanism of PAA on arsenopyrite. Single mineral flotation results showed PAA to have a massive depressive effect on arsenopyrite, reducing its froth recovery from 90% to 3% but only marginally affecting the froth recovery of chalcopyrite. Mixed minerals and bench-scale flotation tests further verified that PAA was an efficient arsenopyrite depressant. Adsorption test results, meanwhile, indicated that PAA could significantly reduce the adsorption of xanthate on the surface of arsenopyrite, but not on that of chalcopyrite. Zeta potential measurements, on the other hand, suggested a strong interaction between the surface of arsenopyrite and PAA compared with chalcopyrite, which induced a positive shift of zeta potential on the arsenopyrite surface. XPS analysis demonstrated that PAA only slightly oxidizes the surface of chalcopyrite, and a very small amount of iron oxide, sulfur oxide and copper oxide were generated, indicating that the surface was still hydrophobic. On the contrary, PAA could strongly oxidize the surface of arsenopyrite and generate a large number of oxygen-containing species, such as As(III)–O, As(V) − O, Fe(III) − O, Fe(III)–SO, SO3 2−, and SO4 2− . This was supported by measuring the contents of these oxides of iron, sulphur, and arsenic on the surface of arsenopyrite, which were found to increase from 47.13% to 88.56%, 14.95% to 45.49%, and 45.94% to 81.57%, respectively. Finally, hydrophilic oxide films containing AsO2 −, AsO3 −, SO3 2−, Fe(OH)3, FeAsO4, and Fe2 (SO4 )3 were formed on the arsenopyrite surface, which further contributed to its depression.